Interrogating Modernity
XXV, 277 p. 4 illus.
Keywords: Interrogating Modernity returns to Hans Blumenberg's epochal The Legitimacy of the Modern Age as a springboard to interrogate questions of modernity, secularisation, technology and political legitimacy in the fields of political theology, history of ideas, political theory, art theory, history of philosophy, theology and sociology. That is, the twelve essays in this volume return to Blumenberg's work to think once more about how and why we should value the modern. Written by a group of leading international and interdisciplinary researchers, this series of responses to the question of the modern put Blumenberg into dialogue with other twentieth, and twenty-first century theorists, such as Arendt, Bloch, Derrida, Husserl, Jonas, Latour, Voegelin, Weber and many more. The result is a repositioning of his work at the heart of contemporary attempts to make sense of who we are and how we’ve got here. Agata Bielik-Robson is a Professor of Jewish Studies at theUniversity of Nottingham, UK and at the Institute of Philosophy and Sociology of the Polish Academy of Sciences in Warsaw, Poland. Daniel Whistler is Reader in Modern European Philosophy at Royal Holloway, University of London, UK.